Engineering circuit analysis - Irwin, J. David; Nelms, R. Mark (John Wiley & Sons Singapore Pte. Ltd, 2022)
Circuit analysis is the fundamental gateway course for computer and electrical engineering majors. Irwin and Nelms' Engineering Circuit Analysis has long been regarded as the most dependable textbook on the subject. Focusing on the most complete set of pedagogical tools available and student-centered learning design, this book helps students complete the connection between theory and practice and build their problem-solving skills. Key concepts are explained multiple times in varying formats to support diverse learning styles, followed by detailed examples, including application and design examples. These are then followed by Learning Assessments, which allow students to work similar problems and check their results against the answers provided. At the end of each chapter, the book includes a robust set of conceptual and computational problems at a wide range of difficulty levels. This International Adaptation enhances the coverage of network theorems by adding new theorems such as reciprocity, compensation, and Millman's, and strengthens the topic of filter networks by including cascaded and Butterworth filters. This edition also includes inverse hybrid and inverse transmission parameters to describe two-port networks and a dedicated chapter on diodes.